Effect of Brand Experience on Customer Engagement Through Quality Services of Online Sellers to Students in Bekasi - Merdiaty, Netty; Aldrin, Neil (Frontiers in Psychology, 2022)
Customer engagement refers to the emotional attachment a student experiences as a customer during repeated and ongoing interactions. Engagement occurs through satisfaction, loyalty, and excitement about the brand experience. Organizations engage customers at the point of behavioral change by exploring opportunities for emotional connection through continuous and consistent positive experiences. When customers engage with a brand experience, they feel emotionally connected and excited about the product and the service quality. This study’s purpose is examining the effect of brand experience on customer engagement by using service quality as a mediator variable; this research was conducted by collecting data from 254 students of the iGeneration born in 1995. Overall, 254 students participated in this study. Of them, 172 people or 68% of the total respondents in this study were women, and 82 people or 32% were males. The results show no direct effect of brand experience on customer engagement, and there is a role for service quality mediators that mediate brand experience and customer engagement. The results are discussed, and the implications for the organization are mentioned.